Using Indigenous stories in caribou co-management - Walter Bayha (Rangifer, 2012)
One day my dream would be to write a policy in my own language and let somebody else interpret. I think my days of interpreting are going down steadily. I’d rather just talk my language these days and leave it at that. As an officer I used to do a lot of judging. I was trained to do that. After I left the Wildlife Service, my wife said to me, “How come you don’t ask those questions anymore?” I said, “I don’t have to. I don’t need to. I just want to be a Dene, like the wildlife out there. Continue being a human being.” As a Dene person I’m taught to listen, to respect people, especially in learning centres because those are like my grandfather. I was taught never to ask questions. I don’t, out of respect. We don’t do that today anymore. The first thing I learned in school was the word “why.” I can think right back when I was growing up as a small child there was no word “why” or “what for.” I had to learn very quickly that if I’m going to be a human being in the future, then I’m going to have to start behaving so that my people will live. Our history is written on the land, in the placenames and the stories, in the language. It’s so important. Our people are disappearing very quickly.